Characterization of Campylobacter jejuni isolated from dogs and humans using flaA-SVR fragment sequencing in Ismailia, Egypt. (August 2021) - Abdelmageed, Hend A.; Mandour, Ahmed S.; El Gedawy, Attia A.; Fawzy, Mohamed; Furuya, Tetsuya; Ezzat, Mahmoud
Highlights: Occurrence of Campylobacter jejuni was investigated in some dogs and humans in Ismailia City, Egypt. Campylobacter jejuni was considerably occur in symptomatic and asymptomatic dogs and humans . Molecular typing of C. jejuni-associated virulence genes and flaA-SVR gene sequencing were performed. Comparative sequence analysis of C. jejuni flaA-SVR fragment in dogs and humans indicated a high identity percentage . We suggested that C. jejuni reservoirs dogs are a public health alarm in Egypt's community. Abstract: Introduction: Dogs are known as asymptomatic carriers for Campylobacter jejuni . The number of pet dogs is increasing in Egypt in the last decade. Objective: This study aimed to investigate the frequency of C. jejuni infection in dogs and humans, molecular typing of associated virulence genes, and flaA-SVR gene using sequencing. Methodology: 152 unpaired fecal swabs from dogs (n = 72) and humans (80) were examined for the presence of C. jejuni and Campylobacter 23S rRNA, and the pathogenicity genes including mapA genes, virB11, flaA, wlaN, iam, tetO, and aadA genes. Sequencing of the flaA- amplicon was also performed for the representative isolates. Results: The isolation rate of C. jejuni was 20.8 % and 31.2 %, respectively in dogs and humans, and all isolates were tested positive for 23S rRNA and mapA genes. C. jejuni harbor virB11 and wlaN ( 20 %, 0%), iam (10 %, 20 %), tetO and aadA1 ( 40 %, both), and flaA ( 40 %, 20 % ) in human and dog strains, respectively. The flaA-SVR sequences revealed high identity between human and dog isolates (94.8 %), but revealed 18 substitutions in the amino acid sequence, and showed that the dog and human C. jejuni were close to strains isolated from human and poultry sources. Conclusion: this study demonstrated the comparative sequence analysis of C. jejuni flaA-SVR fragment in dogs and some Egyptians, which indicated a high identity percentage between them. The results suggest that C. jejuni reservoirs dogs is an alarming public health concern and effective hygienic measures are necessary for house-holding pets to prevent C. jejuni zoonosis in Egypt's community.